Criminology and war transgressing the borders - Walklate, Sandra; McGarry, Ross (Routledge studies in crime and society, 2015)
It is widely observed that the study of war has been paid limited attention within criminology. This is intellectually curious given that acts of war have occurred persistently throughout history and perpetuate criminal acts, victimisation and human rights violations on a scale unprecedented with domestic levels of crime. However, there are authoritative voices within criminology who have been studying war from the borders of the discipline. This book contains a selection of criminological authors who have been authoritatively engaged in studying criminology and war. Following an introduction that 'places war within criminology' the collection is arranged across three themed sections including: 'Theorising War, Law and Crime', 'Linking War and Criminal Justice', and 'War, Sexual Violence and Visual Trauma'. Each chapter takes substantive topics within criminology and victimology (i.e. corporate crime, history, imprisonment, criminal justice, sexual violence, trauma, security and crime control to name but a few) and invites the reader to engage in critical discussions relating to wars both past and present. The chapters within this collection are theoretically rich, empirically diverse and come together to create the first authoritative published collection of original essays specifically dedicated to criminology and war. Students and researchers alike interested in war, critical criminology and victimology will find this an accessible study companion that centres the disparate criminological attention to war into one comprehensive collection.